A guide to Bible translation: people, languages, and topics - Noss, Philip Andrew; Houser, Charles (History of Bible translation, 2019)
"This Guide offers an overview of theory and practice in Scripture translation from ancient times to the present--with an eye to the future. The Guide's 726 articles by 180 contributors are addressed to a global readership of Bible translators, students of culture and biblical studies, as well as interested church members and clerical leaders."--Publisher